2005
DOI: 10.1373/clinchem.2005.051847
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Intact Hemoglobin and Oxaliplatin Interaction by Nanoelectrospray Ionization Tandem Mass Spectrometry

Abstract: Background: Mass spectrometric (MS) detection of intact hemoglobin (Hb) adducts presents considerable analytical challenges because of the noncovalent association of the 4 subunits of Hb, and MS characterization of the interaction of intact Hb with platinum drugs has not been reported. We developed a technique for detecting intact Hb and its drug adduct and studied the interactions between intact Hb and oxaliplatin. Methods: We incubated a series of mixtures of Hb and oxaliplatin at 37°C for 24 h or 5 days to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Evaluation of the number of substitutions of the ␣-and ␤-chain revealed that some of the most frequently possible variants were rarely found, such as in the ␣-chain Leu3 Gln (15 possible variants, 0 detected) and Ala3 Ser (21, 2), or in the ␤-chain Ala3 Ser (15, 1) and Ala3 Gly (15,2). On the other hand, some substitutions are frequently found, such as His3 Arg (10,8) or Lys3 Asn (11,11) in the ␣-chain or Ala3 Asp (14, 13) and Gly3 Asp (12,12) in the ␤-chain.…”
Section: Database Evaluation and Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the number of substitutions of the ␣-and ␤-chain revealed that some of the most frequently possible variants were rarely found, such as in the ␣-chain Leu3 Gln (15 possible variants, 0 detected) and Ala3 Ser (21, 2), or in the ␤-chain Ala3 Ser (15, 1) and Ala3 Gly (15,2). On the other hand, some substitutions are frequently found, such as His3 Arg (10,8) or Lys3 Asn (11,11) in the ␣-chain or Ala3 Asp (14, 13) and Gly3 Asp (12,12) in the ␤-chain.…”
Section: Database Evaluation and Calculationsmentioning
confidence: 99%
“…ESI or MALDI-TOF MS is now becoming a common auxiliary method applied in routine Hb analysis. The use of MS techniques has led to the discovery of more than 60 new mutations (14 ), and even the intact Hb tetramer can be analyzed using a nanoESI MS technique (15 ). Furthermore, MALDI-TOF MS is a highly sensitive method that enables the analysis of Hb chains from a single red blood cell (16 ).…”
mentioning
confidence: 99%
“…The instrumental and experimental conditions have been described in detail in previous studies. [21][22][23][24][25] Horse heart myoglobin (Sigma-Aldrich, St. Louis, MO, USA) was used to externally calibrate the nanoESI-MS instrument. HPLC-grade water and ammonium acetate (Fisher Scientific, Fair Lawn, NJ, USA) were used throughout the experiments.…”
Section: Nanoesi-msmentioning
confidence: 99%
“…In each of these mass spectra, the three clusters of peaks correspond to the 19 erythrocytes from the healthy volunteer who was not under any platinum drug treatment or medication is characteristic of normal intact Hb. 25 The nanoESI mass spectra of the erythrocytes from the cancer patients undergoing oxaliplatin treatment (patients 3, 7, and 14, Figs (Figs. 4(B), 4(C), and 4(D)).…”
Section: Quantification and Profiling Of Oxaliplatinprotein Complexesmentioning
confidence: 99%
See 1 more Smart Citation